Efficacy, safety, and quality of life 4 years after valoctocogene roxaparvovec gene transfer for severe hemophilia A in the phase 3 GENEr8-1 trial - Andrew D. Leavitt; Johnny Mahlangu; Priyanka Raheja; Emily Symington; Doris V. Quon; Adam Giermasz; Maria Fernanda López Fernández; Gili Kenet; Gillian Lowe; Nigel S. Key; Carolyn M. Millar; Steven W. Pipe; et al. (Research and Practice in Thrombosis and Haemostasis)
Background: Valoctocogene roxaparvovec, an adeno-associated virus-mediated gene therapy for severe hemophilia A, enables endogenous factor (F)VIII expression and provides bleed protection. Objectives: Determine valoctocogene roxaparvovec durability, efficacy, and safety 4 years after treatment. Methods: In the phase 3 GENEr8-1 trial, 134 adult male persons with severe hemophilia A without inhibitors and previously using FVIII prophylaxis received a 6 × 1013 vg/kg infusion of valoctocogene roxaparvovec. Efficacy endpoints included annualized bleed rate, annualized FVIII infusion rate, FVIII activity, and the Haemophilia-Specific Quality of Life Questionnaire for Adults. Adverse events and immunosuppressant use were assessed. Change from baseline was assessed after participants discontinued prophylaxis (scheduled for week 4). Results: Median follow-up was 214.3 weeks; 2 participants discontinued since the previous data cutoff. Declines from baseline in mean treated annualized bleed rate (−82.6%; P < .0001) and annualized FVIII infusion rate (−95.5%; P < .0001) were maintained from previous years in the primary analysis population of 112 participants who enrolled from a noninterventional study. During year 4, 81 of 110 rollover participants experienced 0 treated bleeds. Week 208 mean and median chromogenic FVIII activity were 16.1 IU/dL and 6.7 IU/dL, respectively, in 130 modified intention-to-treat participants. Seven participants resumed prophylaxis since the previous data cutoff. Mean change from baseline to week 208 in Haemophilia-Specific Quality of Life Questionnaire for Adults Total Score (P < .0001) remained clinically meaningful for modified intention-to-treat participants. Alanine aminotransferase elevation was the most common adverse event during year 4 (56/131 participants); none required immunosuppressants. Conclusion: Valoctocogene roxaparvovec provides persistent FVIII expression, hemostatic control, and health-related quality of life improvements with no new safety signals.